The Effect of using Facebook Group towards students’ Writing Skill - Terasne (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
The aim of this research was intended to know significance effect of using Facebook toward students’ writing skill. This was a quasi-experimental research in which the researchers employed the two group designs. Both of experimental group and control group were given of pre-test and post-test with different treatment where experimental group treated using Facebook group but control group without face book group. The population of this research was all the second grade students of MA Darrul Muhibbin Praya consist of 86 students. The sample for this research was divided into two classes IIA consisted of 44 students as the experimental group and IIB as the control group and for IIB consist of 42 as the experimental group taken by using lottery. The data collection was done through writing test. Data obtained for the students’ writing skill from the two groups were analysed using t-test formula to determine the degree of significant of the differences between two groups. From the writing test data analysis, it was found that the mean score of experimental class was higher than the mean score of control class (MX= 19.18 > MY = 8) then further analysed using t-test, found that t count > t table, where t-count = 2.90 and t-table = 1.99 at 5% level of significant and according to the existing criteria that the differences between control group and experimental group were significant.